Cancer II - Waring, Michael J. (Topics in Medicinal Chemistry,, 2018)
This book reviews recent breakthroughs in anti-cancer drug discovery. Building on the previous volume in the series, it outlines some of the most significant developments that have occurred in the field in the subsequent period that have led to new drug approvals or promising clinical candidates. The volume is divided into chapters that each relate to a specific protein or protein class. Each chapter provides an overview of the underlying biology and then emphasises the medicinal chemistry strategies and tactics that led to the most significant drugs and drug candidates. A summary of clinical data and the future outlook for the field is also provided. Each chapter is authored by experts in the topic and who have themselves made significant contributions to their respective fields.